2019
DOI: 10.1186/s12885-019-5287-z
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the Tau protein serum level in metastatic breast cancer patients and its correlation with brain metastases

Abstract: BackgroundMetastatic breast cancer (MBC) prognosis is variable, depending on several clinical and biological factors. A better prediction of a patient’s outcome could allow for a more accurate choice of treatments. The role of serum biomarkers in predicting outcome remains unclear in this setting. Tau, a microtubule-associated protein, is a neuronal marker that is also expressed in normal breast epithelial cells and cancer cells. Its tissue expression is associated with prognosis in MBC. However, the prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 47 publications
2
24
1
Order By: Relevance
“…Frisardi et al, 2010;Tucsek et al, 2014). It also supports findings that more aggressive and heterogenous BC tumors express APPs and, consequently, require more complex treatment regimens (Ames et al, 2014;Darlix et al, 2019;Pandey et al, 2016). We found no correlations between concentrations of Ab-42, Ab-40, and tau and those of the 13 cytokines.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Frisardi et al, 2010;Tucsek et al, 2014). It also supports findings that more aggressive and heterogenous BC tumors express APPs and, consequently, require more complex treatment regimens (Ames et al, 2014;Darlix et al, 2019;Pandey et al, 2016). We found no correlations between concentrations of Ab-42, Ab-40, and tau and those of the 13 cytokines.…”
Section: Discussionsupporting
confidence: 90%
“…Over the past decade, researchers have studied peripheral Ab and tau mostly within the context of neurodegeneration, brain injury, and cognitive impairment. Recently, however, oncology research has begun to consider these factors in relation to breast tumor characteristics and brain metastases (Darlix et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Figure 8A , although its exact molecular mechanism and function in cancer have not yet been elucidated. Besides, many studies showed that the aberrant expression of MAPT in many cancers, such as neuroblastoma, breast, and prostate cancer 6,7,25 . Nonetheless, the survey about MAPT in HCC was still lacking.…”
Section: Ppi and Go Enrichmentmentioning
confidence: 99%
“…Previous research demonstrated that higher serum levels of MAPT were independently related to poor prognosis in patients with metastatic breast cancer 6 .…”
Section: Introductionmentioning
confidence: 96%